Optimal economic dispatch to minimize load shedding and operation cost for networked microgrids - Gan, Chin Kim; Al-Areqi, Khaldon Ahmed Qaid; Khamis, Aziah (Springer Verlag, 2023)
In this paper, an optimal economic dispatch model is proposed for networked microgrids in normal and contingency operations using particle swarm optimization. To solve the optimal economic dispatch problem, a summation of two objective functions is formulated, which is to minimize the amount of load to be shed and operation cost of the networked microgrids. The performance of the proposed optimal economic dispatch model was evaluated for several scenarios in independent and networked modes based on two IEEE 9-bus test systems. An analytical model based on optimal power flow was developed to identify the optimal buses of the microgrids that should be linked to form the networked microgrids. The results indicate that the proposed model minimizes the operation cost by up to 2.8% and minimizes the amount of load to be shed by up to 5.6% of the networked microgrids. Moreover, the findings show that the operation of the microgrids is more favorable when the microgrids operate in networked mode compared with that when the microgrids work independently, and the cooperation strategy for power sharing significantly reduces the amount of load to be shed for the microgrids.